PERAN SINERGIS GURU DAN ORANG TUA DALAM MENANAMKAN NILAI BUDI PEKERTI PADA ANAK USIA 5-6 - Rosyidah, Yuni Rahmawati; Zahro, Ayu Fatimatus; Harliana, Harliana (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This research stems from the issue of character decline, evidenced by the rampant inequality in various settings, particularly in educational institutions. This study aims to analyze the influencing factors and how these issues can be addressed effectively. This research employed descriptive qualitative methods, with data collection consisting of observations and interviews with respondents at the KB Budi Utomo Early Childhood Education Center (PAUD) in Sumber Anyar, Jatibanteng, Situbondo. The results of this study indicate a fairly good implementation of character values, particularly in character education, among children aged 5-6 years. This early stage is characterized by respondents' relevant use of policies, planning, and daily implementation, supported by collaborative efforts between teachers and parents both inside and outside the classroom. Therefore, it can be concluded that this synergistic activity is running as intended. The findings indicate that not all parents share the same approach to building education, starting from the family. This occurs due to several factors, such as parents' workloads requiring them to send their children to school.